Sight near the house at the Hudson river where Kudlich lived: Hoboken (New York). Where now are the Bremer and Hamburger Docks
Sight near the house at the Hudson river where Kudlich lived: Hoboken (New York). Where now are the Bremer and Hamburger Docks.